2015
DOI: 10.1016/j.jand.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Eating Frequency and Time of Intake on Nutrient Quality and Body Mass Index: The INTERMAP Study, a Population-Based Study

Abstract: Background Epidemiologic evidence is sparse on the effect of dietary behaviors and diet quality on body mass index (BMI) that may be important drivers of the obesity epidemic. Objective This study investigated the relationships of frequency of eating and time of intake to energy density, nutrient quality and BMI using data from the INTERnational study on MAcro/micronutrients and blood Pressure (INTERMAP) including 2,696 men and women aged 40-59 from the United States and the United Kingdom. Design INTERMAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
124
4
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 40 publications
(49 reference statements)
11
124
4
9
Order By: Relevance
“…Total energy intake and the proportion of total energy intake from snacks was also higher. Previous research has shown that later timing of the last EO [34], consuming a higher proportion of total energy intake after 17:00 h [11, 12] or at the dinner meal [35] and having a higher evening to morning energy intake ratio [36] is positively associated with higher overall energy intakes. However, the metabolic implications of this later eating pattern are unclear, and future research should examine the relationship between temporal eating patterns and health.…”
Section: Discussionmentioning
confidence: 99%
“…Total energy intake and the proportion of total energy intake from snacks was also higher. Previous research has shown that later timing of the last EO [34], consuming a higher proportion of total energy intake after 17:00 h [11, 12] or at the dinner meal [35] and having a higher evening to morning energy intake ratio [36] is positively associated with higher overall energy intakes. However, the metabolic implications of this later eating pattern are unclear, and future research should examine the relationship between temporal eating patterns and health.…”
Section: Discussionmentioning
confidence: 99%
“…The number of dietary data days also varied from as few as 1-7 d. BMI was assessed as a continuous variable expressed as kg/m 2 or as z-scores in some studies (27,(37)(38)(39)(40) , whilst in others BMI was treated as a categorical variable (41,42) . One study selected subcutaneous and visceral fat as an outcome of interest (43) .…”
Section: Characteristics Of Observational Studiesmentioning
confidence: 99%
“…Studies have reported a progressive lowering of insulin sensitivity and glucose tolerance into the evening, which explains how a later temporal eating pattern may promote weight gain (58)(59)(60). Two cross-sectional studies have found a positive association between evening EI and BMI (13,61). In addition, in a crossover trial in 6 healthy lean volunteers that controlled for total EI and macronutrient intake (59), higher glucose concentrations and diminished insulin sensitivity were observed in participants who consumed a large evening meal that was high in energy (w59% total EI) and carbohydrates, but low in fiber, compared with those who consumed that same meal in the TABLE 4 Associations between temporal eating patterns and BMI and overweight or obesity among Australian men and women TEMPORAL EATING PATTERNS AND ADIPOSITY morning.…”
mentioning
confidence: 99%
“…The inconsistent findings among observational studies may be attributed to differences in how the timing and distribution of EI or EOs were assessed. For example, studies have examined the proportion of total EI across stratified time periods (e.g., morning, midday, or evening) (13), the proportion of EI consumed after 1700 (12), and the ratio of evening to morning EI (61). However, because individuals have multiple EOs across the day and the EIs at these EOs are likely correlated, novel approaches, such as the use of LCA or cluster analysis [e.g., the approaches used in this study and in the study by Eicher-Miller et al (17)] are needed to better understand the relation between temporal eating patterns and obesity.…”
mentioning
confidence: 99%